Pattern of Antenatal Care Received by Working Mothers and Their Pregnancy Outcome - Happy, Taslima Akber; Hasan, Mohd Raisul; Rahman, Tania; Yesmin, Laila; Yeasmin, Ayesha; Biswas, Sailendra Nath; Haque, Md Mahmudul (KYAMC Journal, 2022)
Background: Now a days, women are joining almost in every sector of the workforce. In view of these changes, it is necessary to find out whether the health of the working mother or their progeny has been consequently compromised. Objectives: To identify the utilization pattern of Antenatal Care (ANC) received by working mothers and their pregnancy outcome. Materials & Methods: A cross-sectional study was conducted on 242 admitted working mothers with a history of recent delivery in Dhaka Medical College Hospital (DMCH), Dhaka from January 2013 to December 2013. Results: Majority (61.2%) of the mothers was in the age group of 20-30 years with an average income 4885.95 Tk. Two fifth (42.1%) of them were garment workers. Only one-third (33.9%) mother received regular ANC. Majority (79.3) of them received their ANC from doctors and rest of them from Non-Government Organizations (NGO) workers (11.6%), nurses (2.5%) and health assistant (1.7%). Mothers with a history of irregular ANC showed almost 5 times more likely to develop anemia than the mothers with history of regular ANC (p < 0.001). Mean level of birth weight was highest among regularly ANC taking group found in one-way ANOVA (F = 7.24, P<0.05). Conclusion: As ANC has direct effect on a mother’s health and pregnancy outcome employers should have ANC policy for their women workers. KYAMC Journal Vol. 13, No. 02, July 2022: 86-80